PERAN IBU NYAI DALAM PEMBENTUKAN DAN PENGUATAN HIDDEN CURRICULUM PENDIDIKAN AGAMA ISLAM DI PESANTREN - Suryana (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
Islamic boarding schools are educational institutions that not only transmit religious knowledge but also shape students’ character through lived culture, exemplary conduct, habituation, and sustained social interaction. This study aims to analyze the role of Ibu Nyai in the formation and strengthening of the hidden curriculum of Islamic Religious Education at Al-Choeriyah Cibeas Islamic Boarding School, Singaparna, Tasikmalaya Regency. The study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed interactively through data reduction, data display, and conclusion drawing. The findings reveal that Ibu Nyai holds a strategic position in pesantren life as caregiver, educator, role model, emotional mentor, and key actor in managing students’ activities, fostering moral conduct, strengthening discipline, and maintaining relations with parents and the surrounding community. These roles place Ibu Nyai as a central force in activating the hidden curriculum through exemplary behavior, habituation, daily supervision, and involvement in institutional decision-making. This study concludes that Ibu Nyai is a cultural-pedagogical actor with significant influence on the internalization of Islamic Religious Education values. The findings imply the need to strengthen position of Ibu Nyai in pesantren governance as a strategic component of student character formation.